2014
DOI: 10.1177/0021934714544960
|View full text |Cite
|
Sign up to set email alerts
|

School Performance of Children From Monogamous and Polygamous Families in Nigeria

Abstract: Scholastic success of Nigerian children coming from polygamous (n = 50) and monogamous families (n=156) was compared. No differences between two groups were observed across background variables of demographics, parental education and occupation, or family support

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
(50 reference statements)
0
5
0
Order By: Relevance
“…Among the 23 studies, 17 are about women [ 4 , 9 , 29 43 ], while six other studies focus on the children [ 44 49 ]. Among the studies, 11 of them is from Israel [ 4 , 9 , 30 32 , 34 , 44 46 , 48 , 49 ], three studies from Turkey [ 40 , 41 , 43 ], two studies from Iran [ 36 , 38 ], a study from Uganda [ 29 ], a study from Nigeria [ 47 ], a study from Egypt [ 33 ], a study from UAE [ 37 ], a study from Syria [ 39 ], a study from Tanzania [ 42 ] and a study from Jordan [ 35 ]. The smallest sample size was 66 [ 38 ], and the largest was 2000 [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 23 studies, 17 are about women [ 4 , 9 , 29 43 ], while six other studies focus on the children [ 44 49 ]. Among the studies, 11 of them is from Israel [ 4 , 9 , 30 32 , 34 , 44 46 , 48 , 49 ], three studies from Turkey [ 40 , 41 , 43 ], two studies from Iran [ 36 , 38 ], a study from Uganda [ 29 ], a study from Nigeria [ 47 ], a study from Egypt [ 33 ], a study from UAE [ 37 ], a study from Syria [ 39 ], a study from Tanzania [ 42 ] and a study from Jordan [ 35 ]. The smallest sample size was 66 [ 38 ], and the largest was 2000 [ 35 ].…”
Section: Resultsmentioning
confidence: 99%
“…In terms of social problems [ 44 , 46 ], children with polygamous parents have higher risk of family dysfunction with MD 0.33 (95% CI: − 0.11, 0.77) compared to monogamous marriage. For school achievement, two studies [ 45 , 46 ] reported children with polygamous parents had lower scores compared to monogamous parents and a study [ 47 ] reported that children with polygamous parents had difficulties in understanding subjects such as Mathematics and English.…”
Section: Resultsmentioning
confidence: 99%
“…Children from polygynous families self-reported lower understanding of academic subjects than those from monogamous families in Bamgbade and Saloviita's (2014) research. Cherian's (1994) research reported that corporal punishment negatively affected the academic achievement of children from polygynous and monogamous homes equally, except for girls from polygynous homes.…”
Section: Psychological Health and Well-being Outcomesmentioning
confidence: 86%
“…Statistically significant differences for fathers' education were found in 5 studies, with lower levels and/or fewer years of education found for polygynous fathers than monogamous fathers (Al-Krenawi et al, 2002;Al-Krenawi & Lightman, 2000;Al-Krenawi & Slonim-Nevo, 2008;Elbedour, Bart & Hektner, 2003;Hamdan, Auerbach & Apter, 2009). Two studies found no significant differences in father education between polygynous and monogamous families (Bamgbade, & Saloviita, 2014;Elbedour, Hektner, Morad & Abu-Bader, 2003). The remaining 6 papers did not report the fathers' education history separately.…”
Section: Cultural Context and Demographic Variablesmentioning
confidence: 98%
See 1 more Smart Citation